Status and recent results from the Radio Neutrino Observatory in Greenland (RNO-G) - Rno-g; Aguilar, Juanan; Clark, Brian; Coleman, Alan; Couberly, Kenny; Dasgupta, Paramita; De Kockere, Simon; de Vries, Krijn; Deaconu, Cosmin; DuVernois, Michael; Eimer, Anna; Glaser, C.; et al. (SISSA, 2023)
The Radio Neutrino Observatory in Greenland (RNO-G) is an in-ice radio detector for the detectionof ultra-high energy neutrinos beyond ∼10 PeV. The array is under construction and will consistof 35 stations, with the potential to make the first detection of a neutrino-induced particle showervia the Askaryan emission. Stations operate autonomously and consist of both deep antennasdeployed down to -100m in the ice, and high-gain log-periodic dipole antennas buried near thesurface. In total, seven RNO-G stations were installed during the 2021 and 2022 field seasons and arecollecting data since. Here, we present the current status and performance of the experiment. Wepresent results from first analyses using the deep and shallow components of the instrument.